Rent Seeking in a Market with Morality: Solving a Puzzle About Corporate Social Responsibility - Boatright, John Raymond (Journal of business ethics, 2009)
Rent seeking by lobbying for government favors is generally thought to be wasteful. In view of this wastefulness, it is puzzling that rent seeking by corporations has not been criticized as a failure to be socially responsible or even as an unethical business practice. This article examines the compatibility of rent seeking with corporate social responsibility by utilizing Thomas Dunfee’s idea of a marketplace with morality. This idea is useful for solving this puzzle because in considering whether rent seeking is compatible with corporate social responsibility, it is necessary, first, to define rent seeking, which this article argues is a normative concept, and, second, to find some principled way of identifying rent-seeking behavior. It also solves the puzzle about rent seeking by revealing that the concept of rent seeking itself is of little use in determining whether certain conduct is or is not socially responsible since rent seeking activity cannot be identified without first evaluating which activity is rent seeking.